Peran Experiential Marketing terhadap Perceived Value, Tourist Satisfaction, dan Destination Image dalam Mendorong Revisit Intention pada Desa Wisata Cisadon, Sentul - Ardo Hawari; Usep Suhud; Dewi Agustin Pratama Sari (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The purpose of this study is to examine the effects of: (1) Experiential Marketing on Perceived Value, (2) Experiential Marketing on Tourist Satisfaction, (3) Experiential Marketing on Destination Image, (4) Perceived Value on Revisit Intention, (5) Tourist Satisfaction on Revisit Intention, (6) Destination Image on Revisit Intention, and (7) Experiential Marketing on Revisit Intention. Data were collected through a survey using questionnaires distributed both online and offline. The respondents of this study were individuals who had visited Cisadon Tourism Village, Sentul, Bogor Regency, West Java, at least once within the last three months and were at least 18 years of age. This study employed a non-probability sampling method with a purposive sampling technique. A total of 302 respondents participated in this study. The data were analyzed using Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling (SEM) with the assistance of AMOS software. The results of this study, based on hypothesis testing, indicate that the hypothesis regarding the effect of Experiential Marketing on Perceived Value is accepted and significant, the effect of Experiential Marketing on Tourist Satisfaction is accepted and significant, the effect of Experiential Marketing on Destination Image is accepted and significant, the effect of Perceived Value on Revisit Intention is rejected and not significant, the effect of Tourist Satisfaction on Revisit Intention is rejected and not significant, the effect of Destination Image on Revisit Intention is accepted and significant, and the effect of Experiential Marketing on Revisit Intention is accepted and significant.